Sistem Pengontrol Kecepatan Mobil Ambulans Berbasis IoT Menggunakan NodeMCU ESP8266 - Laia, Juniarti; Nainggolan, Winner Parluhutan (MEANS (Media Informasi Analisa dan Sistem), 2025)
This research introduces an IoT-based speed control system tailored for ambulance vehicles using the NodeMCU ESP8266 microcontroller. The system employs an optocoupler sensor to detect wheel rotation speed and transmits real-time data via Wi-Fi to the Blynk application. The objective is to ensure that the ambulance maintains safe operating speeds, while simultaneously activating alerts for the driver whenever thresholds are exceeded. Performance evaluations were conducted across GPRS, 3G, and 4G networks to assess reliability and responsiveness. The findings reveal a response latency of approximately 1 second on a 4G connection, and up to 3 seconds under GPRS. The proposed system exhibited strong network stability over a 24-hour test period and delivered accurate speed monitoring throughout. The novelty of this work lies in the seamless integration of real-time monitoring and alert mechanisms without reliance on manual intervention. This solution has potential application in improving the operational safety and efficiency of emergency medical transport services in Indonesia.